The state-dependent impact of changes in bank capital requirements - Jan Hannes Lang; Dominik Menno (Deutsche Bundesbank, 2023)
Based on a non-linear equilibrium model of the banking sector with an occasionally binding equity issuance constraint, we show that the economic impact of changes in bank capital requirements depends on the state of the macro-financial environment. In 'normal' states where banks do not face problems to retain enough profits to satisfy higher capital requirements, the impact on bank loan supply works through a 'pricing channel' which is small: around 0.1% less loans for a 1pp increase in capital requirements. In 'bad' states where banks are not able to come up with sufficient equity to satisfy capital requirements, the impact on loan supply works through a 'quantity channel', which acts like a financial accelerator and can be very large: up to 10% more loans for a capital requirement release of 1pp. Compared to existing DSGE models with a banking sector, which usually feature a constant lending response of around 1%, our state-dependent impact is an order of magnitude lower in 'normal' states and an order of magnitude higher in 'bad' states. Our results provide a theoretical justification for building up a positive countercyclical capital buffer in 'normal' macro-financial environments.
Keywords: D21; E44; E51; G21; G28; 330; Bank capital requirements; loan supply; dynamic stochastic equilibrium model; financial accelerator; global solution methods